Perspectiva de la situación fitosanitaria del cultivo de maíz en el cantón Tosagua - Gavilánez Zambrano, Emilio Alejandro (2025)
Phytosanitary diseases cause maize production to decrease by up to 30%, a figure that worries maize producers. Therefore, this study aimed to determine the phytosanitary situation in Tosagua Canton, Manabí Province, through the collection of socioeconomic, productive, and sanitary information to understand the current condition of the canton. The research was carried out in two phases. In the first phase, information was collected through surveys administered to 240 producers from two organizations in Tosagua Canton, Amucont and ProduCom, which included questions on socioeconomic and productive aspects. In the second phase, 50 maize plots were evaluated to determine the level of influence or severity percentage of different leaf spot diseases (Bipolaris maydis, Phyllachora maydis, and Stenocarpella maydis) and pests (Spodoptera frugiperda, Dalbulus maidis, and Diatraea saccharalis). The results showed that the average age of producers ranged between 40 and 50 years (40%), with a low educational level, as 56% had only completed primary education. This demographic profile is associated with limited adoption of new technologies. Financially, producers showed high vulnerability, depending on their own resources (61%) to finance their crops, and 32% lacked health insurance. Additionally, 51% did not receive technical assistance, which may limit the adoption of efficient agricultural practices. Forty-five percent applied three fertilizations during the crop cycle, and 56% used NPK fertilizers. A high percentage of producers correctly identified pests such as the fall armyworm (92%) and the stem borer (80%). However, 16% did not recognize the leafhopper, and the Amucont organization was the most affected by the fall armyworm.